Interdependent Sampling and Social Influence - Denrell, J; Le Mens, G (2007)
Most explanations of social influence focus on why individuals might want to agree with the opinions or attitudes of others. The authors propose a different explanation that assumes the attitudes of others influence only the activities and objects individuals are exposed to. For example, individuals are likely to be exposed to activities that their friends enjoy. The authors demonstrate that such influence over sampling behavior is sufficient to produce a social influence effect when individuals form attitudes by learning from experience. Even if the experiences of 2 individuals, when they sample an object or event, are independent random variables, their attitudes will become positively correlated if their sampling processes are interdependent. Interdependent sampling of activities thus provides a different explanation of social influence with distinct empirical and theoretical implications.